Research progress on the antiviral immune regulation of ubiquitin ligase F-box family - MENG Xiangbo, LI Tianqi, ZHANG Tong (口腔疾病防治)
The F-box protein (FBP) family is a large and diverse protein family that is present in all eukaryotes. Based on the secondary structure of the C-terminal, FBPs can be classified as FBXW, FBXL, and FBXO. FBPs can form the SCF complex by binding with S-phase kinase-associated protein 1 (SKP1), cullin 1 (CUL1), and ring-box 1 (Rbx1), functioning as E3 ubiquitin ligase. They specifically recognize substrate proteins via the ubiquitin-proteasome pathway and participate in various biological activities, such as cell cycle regulation, transcriptional regulation, apoptosis, and cell signaling transduction. Numerous studies have shown that FBPs play important roles in host-virus interactions. Being the substrate recognition component of the SCF complex, FBPs bind, ubiquitinate (at K-48), and transport substrates for proteasomal degradation. Based on the type of substrate, F-Box family proteins can either exert antiviral or proviral (immune evasive) effects. Some FBPs can specifically recognize and degrade interferon pathway-associated signal molecules via the ubiquitin-proteasome pathway, thereby upregulating or inhibiting interferon signals and regulating host-related immune responses. Additionally, some FBPs can recognize and degrade viral proteins via the ubiquitin-proteasome pathway, thereby inhibiting viral replication and transmission. However, viruses can hijack FBPs to promote the degradation of immunogenic host proteins, resulting in immune evasion. Although several FBP-targeting inhibitors have been developed, there are limited reports on the application of FBPs in antiviral drug research. Given the large number of FBP family members, further research is required on the functions and mechanisms of FBPs in virus-host interactions, to provide novel directions for the development of antiviral drugs.